Chapter I prestiti verbali nei dialetti sloveni del Friuli: tra integrazione aspettuale e biaspettualità - Benacchio, Rosanna (Biblioteca di Studi Slavistici, 2023)
The article analyses the morphological means used by the Slovenian dialects of Friuli in adapting loan verbs to their aspectual system in comparison to the traditional means of expressing verbal aspect in the indigenous Slavic lexicon. In relation to verbs of Slavic origin, the formation of aspectual pairs was mainly realised by means of prefixation to the base verb (thereby perfectivising it), whereas with loans from the adjacent Romance varieties (Friulian, Italian, Venetian) suffixation proves more productive (yielding imperfectivisation). The analysis is carried out on the dialect of Resia as well as those from the Torre and Natisone Valleys. Despite some differences, in all three dialects there is generally a strong tendency to integrate loan verbs into the aspectual systems of these varieties. Biaspectual verbs, on the other hand, are relatively rare except for the particular case of the verbs in -inat in Resian.